The influence of interactive Agility on some physical and skill abilities among male futsal players - Mushtaq, Abdellatif; Habeeb, Maytham (Journal of Physical Education, 2023)
The study aimed to identify the impact of interactive agility on some e physical abilities of futsal players, and the impact of interactive agility on some skill abilities of futsal players in Iraq. The researchers used the experimental approach. The research items were applied to the research subject of (6) players, The researchers reached many conclusions, the most important of which were the interactive agility exercises prepared to play an active role in the development of the physical abilities of futsal players. The interactive agility exercises used in the research had a positive impact on the development of skill performance in futsal players. Through the conclusions, the researchers recommend the inclusion of interactive agility in the training programs for futsal players because of its importance in improving and developing physical abilities.